PERAN PELIBATAN DIRI SISWA SEBAGAI MEDIATOR DALAM HUBUNGAN ANTARA IKLIM KELAS DENGAN SIKAP KREATIF SISWA SD SEKOLAH ALAM - Rahmi, Rafika; Salim, Rose Mini Agus (Faculty of Psychology, Diponegoro University, 2017)
The aim of this study is to measure the role of student‟s school engagement as mediator in relations between classroom climate with creative attitude in nature-based school. The background of this research is the needs of creative attitude to face the challenge in the future by create the classroom climate and make the children more involved in school activity. One of the ways to increase creative attitude and school engagement is by creating the classroom climate that support the student‟s need. Nature-based school is one of alternative schools in Indonesia that creates active learning in their classroom climate that encourage students to be more engage, so therefore the students can have creative attitude. This research is done with quantitative methods and non-probability sampling methods for elementary school students from grade 3 until 5 in one of Nature Based School in Jakarta, by giving them three self report questionnaires. This research use three measuring instruments, Inventory Classroom Environment, Creativity Attitude Survey, and School Engagement Measure. Thorugh regression analysis, the results showing the positive correlation between classroom climate and school engagement (r = .373; p = .006) and creative attitude (r = .217; p = .002). Through the mediation analysis, the results indicated that school engagement had a role as full mediator in relations between classroom climate with creative attitude in nature based school elementary students. This thing define that classroom climate in nature-based school will improve student‟s creative attitude when students involved emotionally, in cognitive and behavioral in school activity.